PERAN OTORITAS JASA KEUANGAN (OJK) TERHADAP SISTEM LAYANAN INFORMASI KEUANGAN (SLIK) PADA KANTOR OJK REGIONAL 8 BALI DAN NUSA TENGGARA - I Gede Andika Yudiana; Ni Wayan Suartini; I Nyoman Gede Supraptha (Nusantara Hasana Journal, 2022)
OJK is still not serious about monitoring potential reporting delays and errors in data input, as evidenced by the number of non-performing loans due to delays and inaccuracies in inputting SLIK data in Bali. The purpose of this study is to be able to examine the influence of the Role of the Financial Services Authority (OJK) on the Financial Information Service System (SLIK) at the OJK Regional 8 Bali Office in Nusa Tenggara. After conducting a literature review and hypothesis preparation, the data were collected through questionnaires on all employees of the OJK Regional 8 Bali and Nusa Tenggara Offices. Afterward, an analysis of the data obtained using multiple regression analysis was carried out. This analysis includes classical assumption tests, multiple regression analysis, hypothesis testing through t and F tests, and coefficient of determination (R2) analysis. The results of the tests conducted showed that the Financial Services Authority variable (X1) had no significant effect and the Financial Services Authority Standard Operating Procedure variable (X2) had a significant effect on the Supervision of the Financial Information Service System (Y) Report. The results of this study are expected to enrich related theories and provide benefits to the community and input or consideration for the OJK in carrying out its duties.